Effect of Temperature in Deep Eutectic Solvent on Chemical Composition and Structure of Lignocellulose from Corncob - Yusi Prasetyaningsih (Equilibrium Journal of Chemical Engineering, 2026)
Agricultural waste biomass has significant potential and can be processed into high-value materials. Corncobs are a biomass source with high cellulose content. Processing lignocellulosic biomass is challenging due to the complex molecular structure of the bonds. Deep Eutectic Solvents (DES) are used to break the lignin bonds of corncob lignocellulose. The delignification process using ChCl-urea at temperatures of 80 °C, 95 °C, and 110 °C for 6 hours was carried out to determine the chemical composition of corncobs before and after pretreatment. The highest cellulose content of 59.85% was obtained at 110 °C. The kinetic energy of molecules increases with higher temperatures, leading to more effective collisions. The cellulose content increases due to the breaking of ether bonds in lignin and glycosidic bonds in polysaccharides, as shown in the FTIR spectra. XRD analysis shows that the crystallinity of corncobs increases after DES pretreatment. In short, this study provides a simple and green method to prepare cellulose and an efficient utilization route of corncob.